Atlas of Dermatology, Dermatopathology and Venereology Cutaneous Anatomy, Biology and Inherited Disorders and General Dermatologic Concepts - Smoller, Bruce; Bagherani, Nooshin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Bringing together thousands of the best dermatologic clinical and pathological photographs and figures from researchers and scientists around the world, this volume focuses on the most prevalent dermatologic disorders as they relate to cutaneous infectious and neoplastic conditions and procedural dermatology. It includes atypical presentations of various disorders, giving insight into differential diagnoses, helping to familiarize the reader with some of the rarest dermatologic disorders. Atlas of Dermatology, Dermatopathology and Venereology Volume 3 is written for dermatologists, dermatopathologists, and residents and summarizes data regarding any dermatologic disorder and syndrome. Each entry includes an introduction, clinical and pathological manifestations, diagnosis, differential diagnosis, and treatment and prognosis. div> .
Cutaneous Infectious and Neoplastic Conditions and Procedural Dermatology -- Virus Infections -- Syphilis and Bacterial Sexually Transmitted Infections -- Viral Sexually Transmitted Infections -- HIV and the Skin -- Bacterial Infections -- Mycobacterial Infection -- Leprosy -- Mycology -- Parasitic Worms and Protozoa -- Diseases Caused by Arthropods and Other Noxious Animals -- Tropical Diseases of the Skin -- Non-melanoma Skin Cancer and Other Epidermal Tumors -- Tumors of the Skin Appendages -- Lentigos, Melanocytic Naevi and Melanoma -- Soft-Tissue Tumors and Tumor-like Conditions -- Cutaneous Lymphomas and Lymphocytic Infiltrates -- Histiocytoses -- Radiotherapy and Reactions to ionizing Radiation -- Dermatological Surgery -- Hair Transplantation -- Lasers and Flashlamps in the Treatment of Skin Disorders -- Minimally Invasive Treatments and Procedures for Aging Skin.
Keywords: Dermatology; Pathology; Dermatology; Pathology; Skin Diseases